IMPROVING CENTRIFUGAL PUMP BY ADDING VORTEX ROTOR - Mihalid, Tihomir; Guzovid, Zvonimir; Sviderek, Stanislav (Journal of Energy Technology, 2024)
The changes of geological conditions of crude oil deposits and in the structure of layers, i.e. aging of drill wells, during the pumping of oil leads to a decrease in deposit pressure, as well as an increase in water, gas and the abrasive particle content in the pumped crude oil. At the same time, productivity is reduced; presently, over 60% of the world supplied oil is pumped with submersible centrifugal pumps powered by electric motors. Continuous improvement of their exploitation characteristics (e.g. flow (supply), pressure (head) and efficiency) is therefore necessary. Clearly such improvements can provide financial and energy savings, and thus have a positive impact on the environment, which is extremely important from the viewpoint of sustainable development. One experimentally and numerically verified method of improving the performance of centrifugal pumps is the method of creating a so-called coherent structure of eddies and turbulence in the peripheral area of the centrifugal vortex rotor mounted at the back side of centrifugal rotor. A new type of pump has been designed, called a "centrifugal vortex pump", which combines the benefits of these two types of pumps: a high value of the head of the vortex pump stage, and a high value of supply and high efficiency of centrifugal stage. Moreover, centrifugal pumps provide higher flow rates with lower pressure, while the vortex pumps give higher pressure, but with lower flow rates. Research on the energy transformations in the centrifugal vortex pump in this work was carried out using numerical simulations of the flow in the centrifugal pump, centrifugal vortex pump, the vortex part of the centrifugal vortex pump, and also by taking measurements of relevant parameters that describe the performance of pumps at their physical models. The measurement results were used as experimental validation of numerical simulations; vice versa, flow visualization derived from the numerical simulation was used to interpret measurements. An assessment of vortex rotor contribution on the head of centrifugal vortex pump was made. The influence of the vortex rotor on the efficiency of the centrifugal vortex pump was compared to a centrifugal pump with the same geometry. In order to better understand the energy transformations that are theresult of interaction between the flow from the channels of centrifugal part of centrifugal vortex rotor and vortices formed at the vortex part of centrifugal vortex rotor and their interactions with the stator, an analysis of the structure of flow was conducted.
Keywords: centrifugal vortex pump; hydrodynamic phenomena; energy transformation; unsteady flow; pump performance curves; energy efficiency; computational fluid dynamics